2004
DOI: 10.1037/1091-7527.22.2.193
|View full text |Cite
|
Sign up to set email alerts
|

Mindfulness-Based Stress Reduction in Women With Breast Cancer.

Abstract: The number of cancer patients seeking complementary mind-body therapies has increased within recent years. The purpose of this study was to investigate the effectiveness of a mindfulness-based stress reduction and relaxation program (MBSR) on stress, state anxiety, mental adjustment to cancer, and health locus of control in 27 women with diagnosed breast cancer. Findings indicated significant decreases in pre-to-post stress and state anxiety levels; also, results showed significant and beneficial changes for m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
63
0
4

Year Published

2006
2006
2022
2022

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 119 publications
(75 citation statements)
references
References 33 publications
8
63
0
4
Order By: Relevance
“…That finding accords with earlier meta-analyses on mbsr for heterogeneous cancer populations that reported small effect sizes for mental health 20 and mood, and moderate effect sizes for distress 21 . However, a recent systematic review 23 reported large effect sizes for mbsr in improving anxiety and perceived stress in breast cancer patients, but only for uncontrolled trials [34][35][36] .…”
Section: Discussionmentioning
confidence: 99%
“…That finding accords with earlier meta-analyses on mbsr for heterogeneous cancer populations that reported small effect sizes for mental health 20 and mood, and moderate effect sizes for distress 21 . However, a recent systematic review 23 reported large effect sizes for mbsr in improving anxiety and perceived stress in breast cancer patients, but only for uncontrolled trials [34][35][36] .…”
Section: Discussionmentioning
confidence: 99%
“…Five mental and behavioral coping strategies have been identified: Fighting Spirit (FS), where the patient accepts the diagnosis with an optimistic attitude; Helpless-Hopelessness (HH), refers to being overwhelmed by the diagnosis; Anxious Preoccupation (AP), is characterized by an anxious preoccupation with the disease; Stoic-Fatalism (FA), reflects a resigned attitude and passive acceptance about cancer; and, Avoidance (Denial), is where patients avoid or deny the notion of having cancer. 6,11 One study with cancer patients demonstrated positive shifts in cancer adjustment after completing the MBSR intervention, 12 yet no study has explored intervention effects in patients suffering specifically with cancer pain.…”
Section: Mental Adjustment To Cancermentioning
confidence: 99%
“…34 The outcomes were stress (measured by a visual analog scale), state anxiety (measured by the State scores of the State-Trait Anxiety Inventory), 35 mental adjustment to cancer (measured by the Mental Adjustment to Cancer Scale), 36 and health locus of control (measured by the Multidimensional Health Locus of Control Scale). 37 The intervention followed the typical MBSR activities of didactic, inductive, and experiential learning about the stress response and mindfulness techniques of sitting meditation, body scan, and hatha yoga, which were conducted over 1.5-hour sessions held once a week for 8 weeks.…”
Section: Published Studiesmentioning
confidence: 99%